MODELS OF MAJOR ADVERSE CARDIAC EVENT RISK USING RESULTS OF EXERCISE STRESS ECHOCARDIOGRAPHY WITH NONINVASIVE CORONARY ARTERY FLOW ASSESSMENT IN PATIENTS WITH ISCHEMIC HEART DISEASE - A. V. Zagatina; N. T. Zhuravskaya; S. A. Sayganov (Рациональная фармакотерапия в кардиологии, 2017)
Ultrasound non-invasive coronary artery imaging contributes to the diagnosis of ischemic heart disease (IHD) in clinical practice. However, data of the prognostic value obtained from a complex analysis of contractility disorders and coronary blood flow parameters during exercise tests in the world literature are still not available. Aim. To develop risk models for adverse outcomes in patients with probable or definite IHD based on the results of a stress test with a noninvasive coronary blood flow study. Material and methods. Medical data of 689 patients with probable or definite IHD who underwent stress echocardiography with satisfactory visualization of the anterior interventricular artery (AIVA) were included in the analysis. All patients had stress echocardiography on a horizontal bicycle ergometer. Registration of coronary blood flow in the middle third of the AIVA was performed at rest and at the peak of the load with calculation of the coronary reserve value. Further patient follow-up lasted 3 years. Models of further negative outcomes were developed on the basis of the stress echocardiography results and of coronary blood flow parameters. Results. Three models that take into account the factors associated with further mortality, mortality/myocardial infarction and sum of negative outcomes were developed in the study. These models divide a cohort of patients with probable or definite IHD into groups of low, medium and very high risks. Factors associated with the risk of death include: age >56 years, load power <100 W, breach of contractility in the blood supply zone of the circumflex artery initially and during exercise, the difference in blood flow velocities in the AIVA<10 cm/s, coronary reserve of AIVA<2. The risk model of death, taking into account these factors, suggests dividing patients into low-risk group if there are ≤2 factors (mortality 0.6% for 3 years), medium risk – from 2 to 4 factors (mortality 1.8%), high risk – ≥5 factors (mortality 10.3% for 3 years). Conclusion. The study of coronary blood flow during stress echocardiography in addition to the analysis of left ventricular contractility in patients with probable or definite IHD contributes to determine the prognosis of further negative outcomes.